2020
DOI: 10.1038/s41598-020-62749-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Curcuma longa and Allium hookeri Co-treatment via NF-κB and COX-2 Pathways

Abstract: Although inflammation is a host defense mechanism, chronic inflammation mediates several diseases, including cancer, allergy, asthma, and autoimmune diseases, and reportedly, it is associated with a 60% mortality rate. There are several reports on the anti-inflammatory effects of Curcuma longa and Allium hookeri. However, although they can be used as culinary materials and have biological effects, they are not effective anti-inflammatory agents. In this study, we evaluated the synergic effect of C. longa and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 44 publications
(42 reference statements)
1
40
0
1
Order By: Relevance
“…Further, increased levels of IgE, IgG1 and mMCP-1 levels were also decreased proving effects of turmeric in allergic disorders mainly, asthma and food allergies (Shin et al, 2015). Various other studies also reported anti-inflammatory effects of C. longa either alone or in combination (Lee et al, 2020).…”
Section: Curcuma Longa L (Turmeric)mentioning
confidence: 92%
“…Further, increased levels of IgE, IgG1 and mMCP-1 levels were also decreased proving effects of turmeric in allergic disorders mainly, asthma and food allergies (Shin et al, 2015). Various other studies also reported anti-inflammatory effects of C. longa either alone or in combination (Lee et al, 2020).…”
Section: Curcuma Longa L (Turmeric)mentioning
confidence: 92%
“…The plant species has been traditionally used to treat many infections. In addition, it has been documented to have a wide spectrum of pharmacological effects, including anti-oxidant ( Tanvir et al, 2017 ), anti-inflammatory ( Lee et al, 2020 ), and anti-cancer ( Ahmad et al, 2020 ) activities. The rhizome of C. longa is the most commonly used part for the medicinal purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Its weaknesses are low water solubility, low absorption from the gastrointestinal tract, poor stability in body fluids, rapid metabolism, and rapid clearance. For these reasons, its therapeutic use in medicine is limited, but great efforts have been made for a long time to investigate suitable usable nanoformulations [ 153 , 154 , 155 ]. Due to the huge number of such described nanoformulations (e.g., Figure 5 ), the overview of which would require a separate paper, only a few reviews or recently published important articles are listed here [ 78 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%